Case Report: Postoperative Recurrence of Adrenal Epithelioid Angiosarcoma Achieved Complete Response by Combination Chemotherapy With Liposomal Doxorubicin and Paclitaxel - Wei, Hangping; Mao, Jie; Wu, Yandan; Zhou, Qinfei (Frontiers in Oncology, 2021)
Background: Primary adrenal epithelioid angiosarcoma is an extremely rare cancer with a poor prognosis. Because of the rarity of this disease, treatment options have not been well-studied. Case presentation: A 51-year-old man was admitted to Zhejiang Cancer Hospital, diagnosed with a recurrence of adrenal epithelioid angiosarcoma. He had undergone a surgical resection seven months earlier. Combination chemotherapy with liposomal doxorubicin and paclitaxel was administered. After two cycles of chemotherapy, his pain was relieved. Computed tomography (CT) suggested that the soft tissue tumour lesions in the surgical area had disappeared, mediastinal and hilar lymph nodes were significantly reduced or had disappeared, and the patient had achieved a partial response (PR). CT after six cycles of chemotherapy indicated that the patient had achieved a complete response (CR). Conclusion: Combination chemotherapy with liposomal doxorubicin and paclitaxel may be a first-line therapy for recurrent or advanced adrenal epithelioid angiosarcoma.